(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2012)
Genetic diversity was assessed for 66 local aromatic rice genotypes to identify parental genotypes having distant relationship through Mahalanobiss D2 statistic. First six principal component axes above unity contributed 90.88% for variation among the genotypes. Yield per plant showed the highest contribution to total divergence followed by grain breadth, days to maturity and others. The genotypes under study were grouped into ten clusters. Clusters III and VII comprised of the maximum number (11) of genotypes when Cluster X possessed single genotype. The lowest inter genotypic distance was recorded between Kalijira-7 and Chinigura when the highest distance was observed between Elai and Rajbhog-2. The highest inter cluster distance was observed between clusters I and V while the shortest distance was carried by the clusters VII and IX. It revealed that the genotypes belonging to cluster I was far diverse from the genotypes under cluster V whereas the genotypes belonging to clusters VII and IX were least diverse. Among the genotypes, Oval Tapl, Sakkorkhora, Black, Dubsail, Rajbhog-2, Badshahbhog-8, Guamori, Elai, Kataribhog and BRRI dhan-38 might be selected from different clusters for different characters for future breeding program. DOI: http://dx.doi.org/10.3329/bjpbg.v25i2.18665